A novel multiplex quantitative DNA array based PCR (MQDA-PCR) for quantification of transgenic maize in food and feed - Rudi, Knut (Oxford University Press, 2003)
We have developed a novel multiplex quantitative DNA array based PCR method (MQDA-PCR). The MQDA-PCR is general and may be used in all areas of biological science where simultaneous quantification of multiple gene targets is desired. We used quantification of transgenic maize in food and feed as a model system to show the applicability of the method. The method is based on a two-step PCR. In the first few cycles bipartite primers containing a universal 5′ ‘HEAD’ region and a 3′ region specific to each genetically modified (GM) construct are employed. The unused primers are then degraded with a single-strand DNA-specific exonuclease. The second step of the PCR is run containing only primers consisting of the universal HEAD region. The removal of the primers is essential to create a competitive, and thus quantitative PCR. Oligo nucleotides hybridising to internal segments of the PCR products are then sequence specifically labelled in a cyclic linear signal amplification reaction. This is done both to increase the sensitivity and the specificity of the assay. Hybridisation of the labelled oligonucleotides to their complementary sequences in a DNA array enables multiplex detection. Quantitative information was obtained in the range 0.1–2% for the different GM constructs tested. Seventeen different food and feed samples were screened using a twelve-plex system for simultaneous detection of seven different GM maize events (Bt176, Bt11, Mon810, T25, GA21, CBH351 and DBT418). Ten samples were GM positive containing mainly mixtures of Mon810, Bt11 and Bt176 DNA. One sample contained appreciable amounts of GA21. An eight-plex MQDA-PCR system for detection of Mon810, Bt11 and Bt176 was evaluated by comparison with simplex 5′ nuclease PCRs. There were no significant differences in the quantifications using the two approaches. The samples could, by both methods, be quantified as containing >2%, between 1 and 2%, between 0.1 and 1%, or <0.1% in 43 out of 47 determinations. The described method is modular, and thus suited for future needs in GM detection.